PERANAN MEDIA ONLINE â€TANOSHIIJAPANESE.COMâ€ SEBAGAI SOLUSI PEMBELAJARAN KANJI DI MASA PANDEMI - Makhsusy Permatasari, Kun; Karyati, Alo (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
During a pandemic caused by the corona virus, all our activities and lifestyle changes. Work, study, socialization and all activities related to physical contact all change. In this case, including teaching and learning activities. The teaching and learning activities that we have been doing in class during this pandemic require that all activities be carried out from home. This automatically changes the habits of both the teacher and the students being taught. The Covid 19 pandemic has not only occurred in Indonesia, but is evenly distributed throughout the world. Therefore, it is necessary to have media that can be used as a means for teaching and learning activities during this pandemic. Based on this, the researchers tried to use the online media "tanoshiijapanese" as a learning solution during online lectures. This study aims to determine whether the use of online media â€œtanoshiijapanese.com is appropriate as a solution to online teaching. This research is a qualitative descriptive study. Data collection was carried out through observation, questionnaires and interviews using google form. The population in this study were fourth semester students. The research sample was 43 students. Data analysis techniques using graphs from google form. The results of this study are expected to be useful for kanji teachers who will teach online